Determining the Organizational Silence Behavior of Nursing Faculty Members and Affecting Factors - Begüm Yalçın; Güzin Ayan (Association of Nurse Managers, 2022)
Aim: The purpose of this study was to determine the organizational silence behaviors of nursing faculty members and the factors that influence them. Method: This descriptive, cross-sectional study was conducted using an online survey of 127 nursing faculty members working in Turkey. The data were gathered using the Organizational Silence Behavior Scale and a 14-item survey for sociodemographic and job-related information and preferences for speaking up. Results: The participants obtained the highest mean score from 'acquiescence silence' (3.33+-.89), and the result of the multiple regression analysis revealed that 'remaining silent because academic career would be negatively affected' had the greatest influence on the subscales of the Organization Silence Behavior Scale. Conclusion: Nursing faculty play an important role in empowering future nurses. To make valuable contributions to nursing, all faculty members should work in an environment without fear and inhibit organizational silence. To improve the nursing profession, deans/directors and policymakers in nursing should support open communication.